Construction of PPP (Partai Persatuan Pembangunan) and PKS (Partai Keadilan Sejahtera) Thought in Understanding Terrorism - Atjih Sukaesih; Yudi Martha Nugraha; Kodarni (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article specifically explains the construction of PPP and PKS's thinking in interpreting terrorism. These two parties are the largest Islamic parties in Indonesia and almost all of their supporters are Muslims. The qualitative research method used in selecting informants or subjects has been selected purposively based on their activities, with the consideration that those selected as informants can explore and articulate their experiences consciously in interviews conducted by the Researcher through written texts sent and received via Whatsapp and email. The conclusions from the results of this study are (1) the reality of terrorism is socially formed; (2) the reality of terrorism is expressed through language; (3) knowledge of terrorism is obtained through social processes; and (4) emphasizes real action with suicide bombings. PPP firmly stated that there are two main roots of the problem, namely the problem of religious and economic understanding. Meanwhile, PKS firmly believes that terrorism is caused by the motive of economic inequality. To judge the issue and actions of terrorism is left to the Government and religious experts who understand the Law/Regulations and religious affairs only, considering that they do not want to make statements that will harm the existence of the Party in the future. Their task as the largest Islamic Political Party in Indonesia is only to monitor, supervise and calm the unrest in society through their representatives in each branch and region by coordinating and providing understanding and knowledge about terrorism issues and actions.